Vehicle Detection, Tracking and Counting - Maqbool, Safoora; Khan, Mehwish; Tahir, Jawaria; Jalil, Abdul; Ali, Ahmad; Ahmad, Javed (2018 IEEE 3rd International Conference on Signal and Image Processing (ICSIP), 2018)
Traffic congestion and occlusions are major problems nowadays in metropolitan cities which leads to an ever growing traffic accidents. Therefore, the need of traffic flux management in order to avoid these congestions, unnecessary time wastage and tragic accidents is very important. Traffic regulation by optimizing timing of traffic control signals is one of the solutions for this purpose. This paper presents a low cost camera based algorithm in order to control traffic flow on a road. The algorithm is based on mainly three steps: vehicle detection, counting and tracking. Background subtraction is used to isolate vehicles from their background, Kalman filter is used to track the vehicles and Hungarian algorithm is exploited for association of labels to the tracked vehicles. This algorithm is implemented on both daytime and night time videos acquiered from CCTV camera and IR camera. Experimental results show the efficacy of the algorithm.